A Strategic management paper for Nestle Philippines, Ice Cream Division - Pia, Wong P. (Animo Repository, 2004)
Nestle Philippines started its ice cream business in 1994, through joint venture company formed with San Miguel Corporation, using the Magnolia brand. Eventually, the joint venture company was fully merged with the Nestle Company. In 1998, Nestle Philippines Ice Cream Division became a wholly-owned subsidiary of Nestle S.A. Today, Nestle Ice Cream, with its new logo, has but one goal in mind to bring fun and delight to every consumer by giving the highest quality and the most innovative products to each and every ice cream lover. This strategic analysis is developed to address issues brought about by various developments in the Ice Cream Industry a generally competitive environment surrounds this industry strong rivalry among present industry players, strong competitive pressures from substitute products, strong bargaining power of the industrys buyers. The heightening competition suggests that the ice cream business remains to be an attractive industry. Even if the ice cream category is a contracting market according to the research manufacturers the re-entry of Magnolia Dairy Ice Cream (a division of San Miguel Corporation) best represents the market. The market dynamics of the Philippine Ice Cream Industry suggests the continuation of Nestle Ice Creams broad differentiation strategy. Differentiation will work best in the ice cream industry because of the following circumstances: There are many ways to differentiate the products and many buyers perceive these differences as having value. Without this condition, profitable differentiation opportunities are very restricted. Buyer needs and uses are diverse. Some buyers prefer one combination of features and other buyers another. The more diverse buyer preferences are the more room companies have to pursue differentiate approaches to differentiation and thereby avoid trying to out-differentiate one another on much the same attributes. Technological change and product innovation are fast-paced and competition revolves around rapidly product features. Rapid product innovation and frequent introductions of next-version help maintain buyer interests in the product and provide space for companies to pursue separate differentiating paths. Thus, the author recommends the re-strengthening of Nestle Ice Cream differentiation strategy. The company should always seek to differentiate its product offering from rivals in ways that appeal to a broad cross-section of the market. It should continue its strategy of tailor-fitting its product to suit the taste and desire of the local market. Successful differentiation will allow Nestle Ice Cream to: Command a premium price for its product offerings Increase unit sales (because additional buyers are won over by the differentiating features) Gain buyer loyalty to its brand (because some buyers are strongly attracted to the differentiating features and bond with the company and its products) Differentiation will enhance Nestle Ice Creams profitability whenever the extra price the product offerings command outweighs the added costs of achieving its differentiation strategy. Nestle Ice Cream differentiation strategy will be supported by Nestle worldwide four pillars (strategy directions), namely, innovation/renovation, being a low-cost operator/highly efficient operations, effective consumer communication, and product availability. With this, the author highly believes that Nestle Ice Creams market leadership position will be retained through its continuous improvement initiatives and proper execution of its differentiation strategy.